Pedagogical approaches to the teaching of ESL/EFL writing: a literature review - Iskandar (Center for Humanities and Innovation Studies, 2020)
Since the dawn time of the teaching of ESL/EFL writing, teachers and researchers have established and developed pedagogical approaches for the purpose of meeting the needs of students. This paper highlights some prominent approaches to ESL/EFL writing that have taken place; starting from earlier approaches, such as form-dominated approach, writer-focused approach, content-based approach, and reader oriented approach, followed by collaborative approach, computer-assisted, and lastly social media approach as the state of the art. Advantages and weaknesses of each approach were elaborated. Polarization between process and product oriented of writing were also highlighted. This study contributes to the understanding of pedagogical approaches that teachers may apply based on their specific context and students’ circumstances.